EKSPLORASI KEPEMIMPINAN POSITIF BERBASIS NILAI KEISLAMAN DALAM MANAJEMEN PENDIDIKAN NAHDLATUL WATHAN - Lalu Abdul Muhyi Abidin; Nurmiati (An-Nahdlah: Jurnal Pendidikan Islam, 2025)
This study aims to explore positive leadership patterns based on Islamic values ​​in the educational management of the Nahdlatul Wathan organization. This study used a qualitative approach with an exploratory case study design involving 15 key informants from regional leaders, branches, tuan guru, and educational institution managers. Data were collected through in-depth interviews, participant observation, and document analysis, then analyzed using thematic analysis. The results show that leadership in Nahdlatul Wathan represents positive leadership integrated with Islamic values, as reflected in moral-spiritual exemplars, collective deliberation practices, service orientation, and strengthening cadre development. These leadership practices contribute to increased trust, cadre loyalty, organizational stability, and the loss of educational institution management, despite conditions of limited material resources. These findings expand the framework of positive leadership by confirming that religious values ​​can serve as a primary source for the formation of effective and meaningful educational leadership. This study provides a theoretical correlation for the development of value-based leadership studies as well as empirical contributions from the context of non-Western Islamic educational organizations